An Examination of Shura Principles in the National Legislation System - Lubis, Rahmad; Nugraha, Iqbal Subhan; Mutakin, Ali; Nuranisah, Nuranisah; Sulaiman, Heri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study examines the application of the shura principle, a concept of deliberation, as one of the key foundations in Islamic governance, within the context of Indonesia's national legislative system. Using a qualitative-descriptive approach, this study aims to analyze the extent to which shura values can be integrated into the process of forming democratic and just laws and regulations. Data were collected through literature studies of Islamic legal sources, legislative documents, and relevant previous research results. The study's results demonstrate that the principle of shura aligns significantly with the principles underlying the formation of national laws and regulations, including those of openness, public participation, and social justice. In addition, the integration of shura principles can strengthen moral and ethical legitimacy in the legislation process, so that it is expected to produce legal products that are more aspirational and in accordance with plural Indonesian values. These findings suggest the need to strengthen the deliberative mechanism at various stages of legislation, including formulation, discussion, and evaluation of laws and regulations, to achieve a more inclusive and interest-oriented legislative system.